12:44 AM
Jun 16, 2023 at 14:59, by Martin Sleziak
Jun 16, 2023 at 14:59, by Martin Sleziak
2

Page 205 of the book Classical Groups and Algebraic K-Theory defines a symplectic module to be an arbitrary quadratic module $(M,h,q)$ over a form ring $(R,\Lambda)$ with $(J,\varepsilon)$ where $J=\operatorname{id}_R$, $\varepsilon=-1$ and $\Lambda=R$. In particular, this implies that $R$ is com...

THe tag no longer exists - probably removed by the tag-pruning script: mathoverflow.net/posts/448993/revisions
2

Page 205 of the book Classical Groups and Algebraic K-Theory defines a symplectic module to be an arbitrary quadratic module $(M,h,q)$ over a form ring $(R,\Lambda)$ with $(J,\varepsilon)$ where $J=\operatorname{id}_R$, $\varepsilon=-1$ and $\Lambda=R$. In particular, this implies that $R$ is com...

12 hours later…
12:59 PM
1

According to the theorem of Malgrange and Ehrenpreis a fundamental solution exists for any PDE with constant coefficients. But I didn't manage to find in the literature an explicit formula for the backward heat equation $u_t+\Delta u=0$. So what is the formula or does the fundamental solution e...

5 hours later…
6:07 PM
Two new tags and . The intention was probably to use the tag .
1

A rational Ramanujan-like series for $\pi^{-m}$ and character $\chi$ is a series with rational parameters which is of the following form: $$\sum_{n=0}^{\infty} \left(\prod_{i=0}^{2m} \frac{(s_i )_{n+x}}{(1)_{n+x}} \right) \sum_{k=0}^{m} a_k (n+x)^k z_0^{n+x} = \frac{\sqrt{(-1)^m \chi}}{\pi^m}.... I have edited the tags on that question. 1 A rational Ramanujan-like series for \pi^{-m} and character \chi is a series with rational parameters which is of the following form:$$ \sum_{n=0}^{\infty} \left(\prod_{i=0}^{2m} \frac{(s_i )_{n+x}}{(1)_{n+x}} \right) \sum_{k=0}^{m} a_k (n+x)^k z_0^{n+x} = \frac{\sqrt{(-1)^m \chi}}{\pi^m}....

5 hours later…
11:38 PM
And now a top-level tag was added, too:
2

A rational Ramanujan-like series for $\pi^{-m}$ and character $\chi$ is a series with rational parameters which is of the following form:  \sum_{n=0}^{\infty} \left(\prod_{i=0}^{2m} \frac{(s_i )_{n+x}}{(1)_{n+x}} \right) \sum_{k=0}^{m} a_k (n+x)^k z_0^{n+x} = \frac{\sqrt{(-1)^m \chi}}{\pi^m}....